The influence of service quality, network Enom 2.0, and customer satisfaction on Telkomsel customer loyalty: A study in the Papua-Maluku area - Setiawan, Heri Aji; Sugiat, Maria Apsari; Azis, Anton Mulyono (International Journal of Innovative Research and Scientific Studies, 2025)
The company's image plays an important role in shaping customer perception of service quality, especially in the competitive telecommunications and digital services industry. A strong image can be a competitive advantage by driving loyalty through a positive perception of service and price. This study aims to analyze the influence of company image, service quality, and price fairness on Telkomsel's customer satisfaction and loyalty in the Papua and Maluku regions. This study uses a causal quantitative method with a deductive approach and a cross-sectional design. The research population is 3,351,130 Telkomsel customers, with a sample of 385 respondents selected using the purposive sampling method. The research instrument is in the form of an online questionnaire consisting of 28 questions and has been tested for validity and reliability. Data analysis was carried out using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that Telkomsel's corporate image has a significant effect on the perception of service quality and price fairness. The perception of service quality and price fairness has a positive effect on customer satisfaction, which in turn has a direct impact on customer loyalty. Customer satisfaction is the main factor in forming loyalty, where satisfied customers are more likely to continue using Telkomsel's services, extend contracts, and recommend them to others, especially in the Papua and Maluku regions.